A Blood Exosomal miRNA Signature in Acute Respiratory Distress Syndrome - Parzibut, Gilles; Henket, Monique; Moermans, Catherine; Struman, Ingrid; Louis, Edouard; Malaise, Michel; Louis, Renaud; Misset, Benoît; Njock, Makon-Sébastien; Guiot, Julien (Frontiers in Molecular Biosciences, 2021)
Acute respiratory distress syndrome (ARDS) is a diffuse, acute, inflammatory lung disease characterized by a severe respiratory failure. Recognizing and promptly treating ARDS is critical to combat the high mortality associated to the disease. Despite a significant progress in the treatment of ARDS, our ability to identify early patients and predict outcome remains limited. The development of novel biomarkers is crucial. In this study, we profiled microRNA (miRNA) expression of plasma-derived exosomes in ARDS disease by small RNA sequencing. Sequencing of 8 ARDS patients and 10 healthy subjects (HS) allowed to identify 12 exosomal miRNAs differentially expressed (padj<0.05). Pathway analysis of their predicted targets revealed an enrichment in several biological processes in agreement with ARDS pathophysiology, such as inflammation, immune cell activation and fibrosis. By quantitative RT-PCR, we validated the alteration of 9 exosomal miRNAs in an independent cohort of 15 ARDS and 20 HS, among which 7 present a high capability in discriminating ARDS patients from HS (area under the curve>0.8) (miR-130a-3p, miR-221-3p, miR-24-3p, miR-98-3p, let-7d-3p, miR-1273a and miR-193a-5p). These findings highlight exosomal miRNA dysregulation in the plasma of ARDS patients which provide promising diagnostic biomarkers and open new perspectives for the development of therapeutics.